کلام کی طاقت: زبان کی برکات اور خطرات: THE POWER OF SPEECH: BLESSINGS AND DANGERS OF THE TONGUE (Al-Aasar, 2025)
There is no doubt that Allah Almighty has created humankind in the best of forms—Ahsan Taqweem—and granted it a position of honor above all other creatures. Among the most remarkable aspects of this distinction is the gift of speech. The power of speech (quwwat-e-goyai) is a profound blessing from Allah, as highlighted in Surah Ar-Rahman: immediately after the verse “He created man,” it is stated, ‘Allamahu al-Bayan’ (“He taught him eloquence”).Despite being a small physical organ, the tongue holds great potential to shape or shatter a person’s moral character. This is why, as narrated in various Islamic traditions, the limbs of the body plead each morning with the tongue to remain upright, for their actions depend upon it. The Prophet Muhammad ﷺ identified the tongue as a primary source of sin and gave the glad tidings of Paradise to those who safeguard their speech and modesty.However, in spite of its significance, there remains a general lack of mindfulness and fear of Allah regarding the use of speech. One of the key reasons is a lack of awareness about the spiritual and ethical weight of spoken words in the sight of Allah.This research article explores the dual nature of speech—its potential as both a blessing and a danger—through the lens of the Qur'an and Sunnah. It examines how even the smallest verbal actions will be accounted for on the Day of Judgment and highlights the responsibility that rests on every uttered word. The study aims to foster deeper awareness in society about the moral implications of speech and to contribute meaningfully to ethical and spiritual discourse in an Islamic framework.